The relationship between spiritual intelligence, emotional intelligence, and self-regulated learning in high school students - Yuzarion Yuzarion; Yusutria Yusutria; Fifi Indrayani Abd Wahab; Felicidade Lourenca Correia dos Santos; Alfaiz Alfaiz; Hengki Yandri; Akhmad Fajar Prasetya; Akhmad Muhammad Diponegoro; Nurul Hidayah (Indonesian Institute for Counseling, Education and Therapy (IICET), 2025)
This study examines the contribution of spiritual and emotional intelligence to self-regulated learning among 300 Indonesian high school students. The main problem addressed is low self-regulated learning, characterized by lack of motivation, procrastination, and infrequent material review. A quantitative ex post facto design with simple random sampling was employed. Data were collected using standardized Likert scales and analyzed via multiple linear regression and independent sample t-tests. Results showed significant associations between spiritual and emotional intelligence and self-regulated learning (R = 0.489, R² = 0.284, F = 15.988, p < 0.001), with partial contributions of 16.1% and 12.8%, respectively. No significant gender differences in self-regulated learning were found. These findings underscore the importance of spiritual and emotional intelligence development to enhance self-regulated learning. Practical implications include integrating spiritual and emotional development modules into curricula, counseling programs, and self-management training.